Plan exportador para Akupana S.A.S. de aguacate hass cultivado en Colombia hacia Genesis Fruit Group S.L. en Valencia- España (2018)
The aim of this work it is carries out an international marketing plan for the company caleña Akupana, who is in conversations with Genesis Fruit, to commercialize avocado hass in the city of Valencia (Spain). By means of a descriptive methodology, where one used primary information supplied by the Company Akupana S.A.S., and secondary sources, it was possible to identify the different conditions and necessary requirements to carry out the export. It was possible to determine that it is necessary to work together with the producers of avocado from the beginning of the sowing until the end, in order offer a fruit without hurts or blemishes, because the external market demands the best quality and they have strict procedure of health, regarding products for human consumption. The European Union has turned into an important partner for Colombia, in addition the avocado of this variety is very accepted and desired by the consumers in this country, which initially were consuming it as an exotic fruit, but on having happened from the time they have begun to incorporate it in his daily diet, taking advantage of the food benefits that the product offers. To export to the EU products as the avocado, duty is not paid, but the normatividad demands to expire strictly with requirements like the packing and packing, the quality of the product, the sanitary certificates, the fulfillment of sanitary procedure from the process of sowing, crop and in the plant of collection. It was possible to conclude that though Mexico is the first exporter of this fruit, Colombia has a great opportunity to turn into an option or alternative, due to the availability of the fruit all the year round, so there is the infrastructure in area and in resources to face to the production. For your part, Akupana has a door opened in the foreign, not alone market to export avocado hass, but also other varieties and different exotic fruits that the company offers; this way it is possible to guarantee and position on the market. At present what needs the company is the major capital for investment, to contract more personal and to qualify the one that exists in topics of exterior trade, to be able to improve the steps of export and to avoid losses for deterioration of the product.